The Sub Lethal Effect of Detergent on the Biochemical Parameter of Fresh Water Fish Catla catla - Regina Mary, R (International Journal of Pharmaceutical & Biological Archive, 2014)
The Sub Lethal Effect of Detergent on the Biochemical Parameter of Fresh Water Fish Catla catla